Mapping the current knowledge on leucocytes in human breastmilk: a scoping review protocol - Juan José Yepes-Nuñez; Claudia Angélica García-Alonso; Brenda Jiménez-López; Sebastián Castaño-Duque; Anna-Maria Lampousi; Erick Sánchez-Salguero; Marion E G Brunck (BMJ Open)
Introduction The immunological composition of breastmilk has gained research interest as breastfeeding has been persistently correlated with improved health outcomes in children. Immune cells, also known as leucocytes, are key components of the body’s immune system, but they remain understudied in breastmilk. The relevance of breastmilk leucocytes for breastfeeding-mediated immune benefits remains controversial. To identify the current state-of-the-art on breastmilk leucocyte research, unearth knowledge gaps and propose research priorities, a scoping review is necessary.Methods and analysis This scoping review will address the general question of what is known about leucocytes in human breastmilk. The development of this scoping review protocol adhered to the recommendations set forth by the Joanna Briggs Institute guidelines. Peer-reviewed research articles published in English, French or Spanish will be eligible for inclusion in the scoping review. The initial literature search was conducted in January 2024 within the Medline, Embase, Cochrane Central and BVS databases.Ethics and dissemination This review does not require ethics approval. Our dissemination strategy includes peer-review publication and presentations at conferences and to relevant stakeholders.Registration details This protocol was registered in Open Science Framework (available at: https://osf.io/kwfsy) on 19 February 2024.